Taming Overconfident CEOs Through Stricter Financial Regulation - Bernhard Kassner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
A large body of literature finds that managerial overconfidence increases risk-taking by financial institutions. This paper shows that financial regulation can be effective at mitigating this type of risk. Exploiting regulatory changes introduced after the financial crisis as a natural experiment, I find that overconfidence-induced risk-taking decreases in financial institutions subject to stricter regulation. Following the easing of these regulations, overconfidence-induced risk-taking increases again. These findings confirm the effectiveness of financial regulation at correcting overconfident behavior, but also suggest that the impact fades away quickly once removed.
Keywords: G28; G32; G38; G40; 330; overconfidence; risk; regulation; financial sector